Assessment of oral health status and periodontal treatment needs among rural, semi-urban, urban, and metropolitan population of Gurgaon District, Haryana State - Harpreet Singh Grover; Amit Bhardwaj; Narender Yadav (Wolters Kluwer Medknow Publications, 2016)
Background: Role of various etiologic factors in periodontal disease has been investigated by means of epidemiologic surveys and clinical studies. The community periodontal index of treatment needs (CPITN) provides a picture of the public health requirements in the periodontal field, which is essential for national oral health policy-making and specific interventions. Materials and Methods: This study was conducted on 4000 individuals among rural, semi-urban, and metro population of Gurgaon District, Haryana State, to find out the oral health status and periodontal treatment needs (TNs) using CPITN index. Results: An inference was drawn from the results that among 4000 participants from all the four population groups' maximum, i.e., 63.80% of individuals needed TN2 whereas 18.20% of individuals needed TN3 and 18.10% of individuals needed TN1. Conclusion: It can be concluded with a word of hope and a word of warning. Hope lies in the fact that the measurement of periodontal diseases by epidemiological study of this condition is improving and receiving wide spread attention. The warning lies in the varied nature of the condition which goes to make up periodontal disease and perplexing ways in which these conditions blend. In addition to dental practitioner, periodontist and public health workers must devote more time and effort toward controlling periodontal disease than they seem to be devoting at present.